The Influence of Technological Innovation, Financial Literacy and Financial Risk on Customer Adoption at Seabank - Wardani, Novita Susila; Pituringsih, Endar (E-Jurnal Akuntansi; Vol 35 No 6 (2025)DO - 10.24843/EJA.2025.v35.i06.p16, 2025)
This study aims to analyze the effect of technological innovation, financial literacy and financial risk on customer adoption in Seabank. Seabank is a digital bank application that is growing rapidly in Indonesia. The sampling technique is purposive sample and determining the sample size with the formula hair et al, resulting in 150 respondents. The analytical tool used is SmartPLS 4. This result of this study supports the Technology Acceptance Model (TAM) showing that technological innovation, financial literacy and security risks on seabank customer adoption have a significant positive effect. The limitations in the study are in the scope and number of samples used, so it is recommended in further research to expand the scope of the study and increase the number and diversity of samples so that the results obtained are more representative and can be generalized. Keywords: Technological Innovation; Financial Literacy; Security Risk; Customer Adoption; Seabank